2022
DOI: 10.3389/fmicb.2022.866930
|View full text |Cite
|
Sign up to set email alerts
|

Tardigrade Community Microbiomes in North American Orchards Include Putative Endosymbionts and Plant Pathogens

Abstract: The microbiome of tardigrades, a phylum of microscopic animals best known for their ability to survive extreme conditions, is poorly studied worldwide and completely unknown in North America. An improved understanding of tardigrade-associated bacteria is particularly important because tardigrades have been shown to act as vectors of the plant pathogen Xanthomonas campestris in the laboratory. However, the potential role of tardigrades as reservoirs and vectors of phytopathogens has not been investigated furthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 103 publications
1
13
0
Order By: Relevance
“…The issue of potential contamination in tardigrade microbiota studies was first mentioned by Tibbs-Cortes et al (2022), who applied a decontamination strategy in the analysis of microbiota of tardigrade communities extracted from environmental samples. A novel component of our study is information regarding the diversity of contamination sources that may affect microbial community profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of potential contamination in tardigrade microbiota studies was first mentioned by Tibbs-Cortes et al (2022), who applied a decontamination strategy in the analysis of microbiota of tardigrade communities extracted from environmental samples. A novel component of our study is information regarding the diversity of contamination sources that may affect microbial community profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that microorganisms present in the environment are also present in tardigrades, and spotted significant differences between the microbiota of fully-fed and starved tardigrades. A recent tardigrade microbiota study conducted by Tibbs-Cortes et al (2022), characterized microbiota of tardigrade communities (tardigrades extracted from samples, without species identification) in American orchards, with the application of decontamination strategy. Using the same samples, the authors observed signs of Rickettsia infection in two of 55 tardigrade individuals using FISH (Tibbs-Cortes et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In 2018-2021, our team discovered Wolbachia infections in Tardigrada [34], Bivalvia [35] and Crustacea [32]. Later, Tibbs-Cortes et al [36] also confirmed Wolbachia infection in the microbiome of Tardigrada. This allows us to suspect that more extensive sequencing would bring more new data of infections in new host taxa, potentially revising our understanding of Wolbachia evolution.…”
Section: Supergroup Host Host-wolbachia Association Referencementioning
confidence: 92%
“…To check whether all Wolbachia infections found in Tardigrada represented the same supergroup, we carried out the phylogenetic reconstructions of tardigrade Wolbachia 16S rRNA sequences identified in our study and in previous surveys [34,36]. All of these sequences were also compared with other Rickettsiales sequences obtained by Mioduchowska et al [34] and Tibbs-Cortes et al [36].…”
mentioning
confidence: 88%
See 1 more Smart Citation